المؤتمر الأفخارستي بقرطاج ماي 1930م وتطور العمل الوطني بتونس - عقيب, محمد السعيد (University of Eloued جامعة الوادي, 2016)
يعالج هذا المقال انعقاد المؤتمر الأفخارستي في تونس من 7 إلى 11 ماي 1930، والظروف المرافقة لتنظيمه، والخطوات المتبعة في الإعداد له، ويتتبع التظاهرات التي رافقت انعقاد المؤتمر، وكذلك ردود الفعل التونسية اتجاهه، ومختلف الأساليب التي استخدمها التونسيون للاعتراض على المؤتمر، وكيفية استغلال الوطنيين التونسيين انعقاد هذا المؤتمر للعودة للنشاط بقوة أكثر مما كانوا عليه سابقا، وانخراط العديد من الفئات في صف الوطنيين للتصدي للسياسة الاستعمارية المتبعة في تونس، مما شكل تطورا هاما في مسيرة الحركة الوطنية من أجل القضية التونسية. Abstract This article deals with the Eucharistic Congress in Tunis from 7 to 11 May 1930, and circumstances associated with it, as well as the steps involved in preparing for it, and we address the demonstrations that accompanied the conference, as well as the Tunisian reactions, and the various methods used by the Tunisians to object to the conference, and how the national Tunisian exploit holding of this conference to return to the activity more strongly, and the involvement of many of the categories in the national row to counter colonial policy followed in Tunisia, Which resulted in creation of an important development in the process of the National Movement for the Tunisian case
The Eucharistic Congress in Carthage May 1930 and the development of national action
مجلة البحوث والدراسات المجلد 13 العدد 02 جامعة الوادي
Keywords: مؤتمر الأفخارستي؛ قرطاج؛ ماي 1930؛ العمل الوطني؛ تونس: History - Tunisia - the Eucharist - colonialism - politics.